Analisis Perilaku Indisipliner Siswa pada Tata Tertib Sekolah di Kelas V SDN 05 V Suku Bawah Kabupaten Agam Provinsi Sumatra Barat - Indris, Gatryn Meilani; Chudari, Ima Ni'mah (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The regulation is one of the rules that purposed to create the student’s discipline attitude. The occurrence of violations of the rules is a form of indiscipline behavior. Indiscipline behavior occurs because of habits that happen repeatedly. If this indiscipline behavior is left unchecked, it will fade the student’s disciplinary attitude. The purpose of this research was to determine the implementation of school rules, to find out the indiscipline behavior of students toward school rules by students from class V, also to find out the causes of that indiscipline behavior by students. The approach used in this research was a qualitative approach with a case study method. Data collection techniques used to support research are observation and interview. Compilation of the data findings using data reduction technique, data presentation, and drawing a conclusion. The result from the field shows that the regulations of the school have three elements, some obligations and prohibitions were written in detail and clearly, then the reprimands as sanctions given to violators, and socialization of regulations that were conducted when the new school year began. The indiscipline behaviors that the students carried out were; school uniforms that did not match the rules, incomplete attributes, wearing colored shoes, leaving books in school drawers, turning back the library books over the borrowing limit, coming late to school, letting trash scattered, did not do the homework, disrespecting and unloving people at school, vandalizing school facilities, destroying school environment, cheating, long nails and long hair for boys. The causes of this indiscipline behavior were the lack of a sense of responsibility in students, peer behavior that can be imitated, a sense of wanting to be noticed, and a lack of parental attention.